Solving a layout design problem by analytic hierarchy process (AHP) and data envelopment analysis (DEA) approach - Tuzkaya, UR; Eser, A; Argon, G (SPIE-INT SOC OPTICAL ENGINEERING, 2004)
Today, growing amounts of waste due to fast consumption rate of products started an irreversible environmental pollution and damage. A considerable part of this waste is caused by packaging material. With the realization of this fact, various waste policies have taken important steps. Here we considered a firm, where waste Aluminum constitutes majority of raw materials for this fir0m. In order to achieve a profitable recycling process, plant layout should be well designed. In this study, we propose a two-step approach involving Analytic Hierarchy Process (AHP) and Data Envelopment Analysis (DEA) to solve facility layout design problems. A case example is considered to demonstrate the results achieved.
Keywords: facility layout; analytic hierarchy process (AHP); data envelopment analysis (DEA); Engineering